BIG DATA ANALYSIS IN MARKETING DECISION MAKING INDUSTRIAL REVOLUTION ERA 4.0: CASE STUDY ON FASHION INDUSTRY IN INDONESIA - Efendi, Bahtiar; Sitorus, Sunday Ade; Firdaus, Firdaus; Indrianti, Merita Ayu; Kraugusteeliana, Kraugusteeliana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The Industrial Revolution 4.0 era has changed the landscape of the world of manufacturing and technology with the integration of digital technology, automation and sophisticated data communications. The fashion industry in Indonesia is also not immune from the major impact of these changes, especially in marketing decision making. Big data analysis is crucial in optimizing marketing strategies by understanding consumer preferences, market trends and competition. However, the use of big data also brings challenges, especially regarding the security and privacy of consumer data. This research adopts a qualitative method with a literature review approach to investigate the use of big data in marketing decision making in the Indonesian fashion industry. The research results show that big data plays an important role in customer segmentation, consumer behavior analysis, trend prediction, and product innovation. The benefits companies gain from implementing big data include deep understanding of consumer behavior, fast decision making, operational efficiency, better risk management, product and service innovation, improved customer experience, and dynamic price adjustments. However, the challenges faced include data security risks, personal identification risks, and compliance with global privacy regulations. Assessment of the readiness of Indonesian fashion industry companies to adopt big data involves evaluating technology infrastructure, data analysis skills, awareness of big data concepts, data security and privacy, understanding customer behavior, technology adoption, ability to process real-time data, budget availability, readiness for innovation, and acceptance of organizational culture. By considering these aspects, companies can evaluate the extent to which they are ready to integrate big data in marketing decision making to achieve success in the Industrial Revolution 4.0 era.